ANALYSIS OF THE EFFICIENCY OF ISLAMIC BANKING PERFORMANCE IN INDONESIA - Choiroini, Roisatul; Jaya, Tiara Juliana (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
This study aims to determine the level of performance efficiency and sensitivity of each variable to the value of performance efficiency in Islamic banking in Indonesia. The method used is the Super Efficiency DEA method, which is a development of the Data Envelopment Analysis (DEA) method to rank each DMU. The purposive sampling technique used resulted in 7 DMUs from Islamic commercial banks that were sampled in this study. There are two kinds of variables used, namely input variables and output variables. Input variables consist of deposits, total assets, and general administrative expenses. Output variables consist of financing, operating income, and investment. The determination of these variables is done through an intermediation approach. The results of this study show that five banks achieve an efficient level; the one with the highest average efficient value is Bank Victoria Syariah at 398.52%. The banks that have yet to reach the efficient level are Bank Muamalat Indonesia at 81.73% and Bank Syariah Indonesia at 69.06%. In addition, the efficiency value of Islamic commercial bank performance is very sensitive to all input variables, namely deposits, total assets, and general administrative costs. While, in the output variable, the performance efficiency value is very sensitive to the financing variable and quite sensitive to the operating income and investment variable.